Mối quan hệ giữa khả năng hấp thu và sự gắn kết của sinh viên: Vai trò điều tiết của tính bền bỉ - Nguyễn Thị Đoan, Trân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
This empirical study demonstrates the relationship between absorptive capacity and student engagement in the university in which they enroll. By applying Structural Equation Modeling to process the model with three latent variables and four hypotheses with respect to the linkages among these variables, the results indicate that three out of four hypotheses are accepted at the significance level of less than 1% and one accepted at 5% significance level with official data collected from 1,263 students at five institutions for economics and business education in Ho Chi Minh City and Hanoi. At the same time, the research also finds that grit not only is an antecedent of absorptive capacity but also plays a role of a mixed moderator to reinforce the relationship between absorptive capacity and student engagement. Therefore, this research result contributes further to the existing literature on student engagement, grit, and absorptive capacity,
Keywords: Student Engagement; Absorptive Capacity; Grit